Study of thermochemical treatments of cork in the 150–400°C range using colour analysis and FTIR spectroscopy - Şen, Ali; Marques, António Velez; Gominho, Jorge; Pereira, Helena (Industrial Crops and Products, 2012)
A study of chemical transformations of cork during heat treatments was made using colour variation and FTIR analysis. The cork enriched fractions from Quercus cerris bark were subjected to isothermal heating in the temperature range 150–400 ◦ C and treatment time from 5 to 90min. Mass loss ranged from 3% (90min at 150 ◦ C) to 71% (60min at 350 ◦ C). FTIR showed that hemicelluloses were thermally degraded ﬁrst while suberin remained as the most heat resistant component. The change of CIE-Lab parameters was rapid for low intensity treatments where no signiﬁcant mass loss occurred (at 150 ◦ C L* decreased from the initial 51.5 to 37.3 after 20min). The decrease in all colour parameters continued with temperature until they remained substantially constant with over 40% mass loss. Modelling of the thermally induced mass loss could be made using colour analysis. This is applicable to monitoring the production of heat expanded insulation agglomerates.
Keywords: Colour analysis; Cork; FTIR; Heat treatment; Quercus cerris

The organosolv fractionation of cork components - Cordeiro, N.; Neto, C. P.; Rocha, J.; Belgacem, M. N.; Gandini, A. (HOLZFORSCHUNG, 2002)
Extractive-free cork from Quercus suber L. was submitted to organosolv fractionation and the effects of different process variables, such as ethanol/water ratio, temperature, time and the presence of acidic or alkaline catalysts, were studied. The variation of the relative proportions of extracted components, as a function of the processing conditions, could thus be established. Whereas the addition of 0.1 M acetic acid only increased the yield of extracted materials from about 15 to 23 %, the use of sodium hydroxide, at the same concentration, produced a jump to 76 %. In the case of the alkaline organosolv fractionation. an increase in process temperature, time and catalyst concentration led to an increase in the extraction yield, although in some cases this increase did not follow a sustained trend, as in the case of reaction time. Increasing the ethanol/water ratio led to a higher selectivity in favour of suberin extraction. Residual cork from different organosolv processes was characterised by FTIR and C-13 solid-state NMR. The latter technique provided some valuable information about both process selectivity and cork morphology, particularly with respect to the positioning of suberin macromolecules in the cell wall.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: C-13 NMR; Cork; ethanol/water extraction; FTIR; organosolv fractionation; Quercus Suber L; suberin